2009
DOI: 10.1128/aac.01413-08
|View full text |Cite
|
Sign up to set email alerts
|

Fenticonazole Activity Measured by the Methods of the European Committee on Antimicrobial Susceptibility Testing and CLSI against 260 Candida Vulvovaginitis Isolates from Two European Regions and Annotations on the Prevalent Genotypes

Abstract: The activity of fenticonazole was studied against 260 West and Southeast European vulvovaginal candidiasis isolates, and low MICs were displayed. Fenticonazole was assessed by European Committee on Antimicrobial Susceptibility Testing and CLSI microdilution methods for the first time, and the results showed excellent agreement (97%) and significant interclass correlation coefficient (P < 0.0001). Also, the levels of agreement for the results for itraconazole, fluconazole, and ketoconazole were 84%, 90%, and 98… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

2
7
2

Year Published

2010
2010
2017
2017

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 16 publications
(11 citation statements)
references
References 33 publications
2
7
2
Order By: Relevance
“…23 Similarly, in the present study, we found that production of cytokines/chemokines elicited by AC was greater than that elicited by PC, both ex vivo and in vivo in a mouse model. This heightened proinflammatory response could be attributed to "albino" AC (lacking pigment) that display strong cell surface β-glucan.…”
Section: Resultssupporting
confidence: 84%
See 1 more Smart Citation
“…23 Similarly, in the present study, we found that production of cytokines/chemokines elicited by AC was greater than that elicited by PC, both ex vivo and in vivo in a mouse model. This heightened proinflammatory response could be attributed to "albino" AC (lacking pigment) that display strong cell surface β-glucan.…”
Section: Resultssupporting
confidence: 84%
“…21 Analysis of physicochemical properties in the RodAp knockouts of the two species also suggests that there may be other differences in the composition of their outer cell walls, i.e., lipid and cells, i.e., Toll-like receptor 4 (TLR4) and mannose receptors, thus modulating stage specific immune responses. 17,20,21,23 Here, we show that the two different conidial types of A. terreus have differential β-glucan display and accordingly are recognized differently by immune cells. The influence of differential patterns of β-glucan presentation on pathogenicity for AC versus PC, and the consequences of altering these patterns, requires deeper investigation.…”
Section: Resultsmentioning
confidence: 66%
“…One reason might be that the strategy of genotyping used by Antonopoulou et al (1) was different from that used in our study. Different genotyping methods may result in different groupings of isolates.…”
Section: Discussioncontrasting
confidence: 39%
“…Interestingly, most of the itraconazoleresistant isolates belonged to a specific genotype (13). Contrary to the report described above, recent susceptibility testing and microsatellite typing of vulvovaginitis-causing Candida isolates from Europe did not find an association between azole resistance and any particular genotype cluster among C. albicans isolates (1). In the present study, fluconazole and itraconazole susceptibilities of the C. albicans isolates with the dominant genotypes CAI 30-45 and CAI 32-46 from VVC patients were compared with those of isolates possessing other minor genotypes and of isolates from the oral cavity by using the standard broth microdilution method.…”
contrasting
confidence: 52%
See 1 more Smart Citation